Self-Help Groups: A Means to Empower Rural Women (Indian Journal of Extension Education, 2013)
Even after 66 years of independence of India, rural women have been the most underprivileged, disadvantaged and discriminated strata of the society. with self help groups are proved as a powerful means. The present study was conducted the aim of analyzing the performance of group members regarding decision-making and economic empowerment. Through interview schedule, the performance details of the group members were obtained. It was found that majority of respondents (69 ) were of medium level of decision making ability and 71 per cent of the respondents had fair access of % resources.